Correlation of radon and geomagnetic anomalies of the territory of Ukraine - Orlyuk, M.I.; Marchenko, A.V.; Yatsevsky, P.I. (Reports of the National Academy of Sciences of Ukraine, 2018)
The appearance and estimation of the radon concentration areas are an urgent task in the study of the environmental safety for the people living. According to the research, radon anomalies are caused by radioactive elements thorium and uranium, which are concentrated in radioactive minerals. In this work, based on the qualitative analysis, the correlation of radon and uranium anomalies with negative magnetic anomalies of regional and local classes and with faults of northwestern and latitudinal directions is revealed. A physico-mineralogical tectonic basis for such a connection is proposed. It is caused, first of all, by a regular decrease in the concentration of ferromagnetic minerals and by an increase in radioactive minerals in the series of changes in the acidity of rocks: ultrabasic—basic—medium—acidic. Therefore, indirectly, the main sources of radon anomalies are granitoids and albitites, which are characterized by the minimum values of magnetization. Thus, a weak magnetization and an increased content of radioactive minerals in these rocks in conjunction with deep faults and zones of cracking explain, in general terms, the relationship of radon and magnetic anomalies.